Binding of the auxiliary subunit TRIP8b to HCN channels shifts the mode of action of cAMP - Hu, Lei (The Rockefeller University Press, 2013)
Hyperpolarization-activated cyclic nucleotide–regulated cation (HCN) channels generate the hyperpolarization-activated cation current Ih present in many neurons. These channels are directly regulated by the binding of cAMP, which both shifts the voltage dependence of HCN channel opening to more positive potentials and increases maximal Ih at extreme negative voltages where voltage gating is complete. Here we report that the HCN channel brain-specific auxiliary subunit TRIP8b produces opposing actions on these two effects of cAMP. In the first action, TRIP8b inhibits the effect of cAMP to shift voltage gating, decreasing both the sensitivity of the channel to cAMP (K(1/2)) and the efficacy of cAMP (maximal voltage shift); conversely, cAMP binding inhibits these actions of TRIP8b. These mutually antagonistic actions are well described by a cyclic allosteric mechanism in which TRIP8b binding reduces the affinity of the channel for cAMP, with the affinity of the open state for cAMP being reduced to a greater extent than the cAMP affinity of the closed state. In a second apparently independent action, TRIP8b enhances the action of cAMP to increase maximal Ih. This latter effect cannot be explained by the cyclic allosteric model but results from a previously uncharacterized action of TRIP8b to reduce maximal current through the channel in the absence of cAMP. Because the binding of cAMP also antagonizes this second effect of TRIP8b, application of cAMP produces a larger increase in maximal Ih in the presence of TRIP8b than in its absence. These findings may provide a mechanistic explanation for the wide variability in the effects of modulatory transmitters on the voltage gating and maximal amplitude of Ih reported for different neurons in the brain.